ANALISIS PENGARUH BEBERAPA FAKTOR KEUANGAN BANK TERHADAP JUMLAH PEMBERIAN KREDIT DI PERBANKAN INDONESIA - Yoyo Cahyadi; Arum Pratiwi Puspitasari (Journal of Business Strategy and Execution, 2015)
Research aims to analyze the effect of DPK, LDR, [1]CAR, NPL, ROA, and BOPO on credit grant in Indonesian banking. Research used quantitative analysis method with multiple regression technique to examine the relationship of one dependent variable and more than one independent variables. Variables used in the study were DPK, LDR, CAR, NPL, ROA, and BOPO as independent variables and the amount of credit grant as dependent variable. Results showed that six independent variables simultaneously affected the dependent variable; and partially, variable DPK and LDR had significant positive influence on the amount of credit grant. Then, the CAR showed no significant positive influence and NPL, ROA, and BOPO showed no significant negative on the amount of credit grant.